Theory, Research and Pedagogy in Learning and Teaching Japanese Grammar - Benati, Alessandro G.; Yamashita, Sayoko; SpringerLink (Online service) (London : Palgrave Macmillan UK(Imprint), 2016)
This edited book focuses on the role of different types of pedagogical solutions in the acquisition of the Japanese grammatical system by reviewing, assessing and measuring current theory and research. Findings from this research have implications for the way Japanese grammar is learned and taught in a classroom context. The editors and contributors address a number of questions around the role of Japanese grammar learning and teaching such as: what is the role of instruction in Japanese second language acquisition? What are the main findings of empirical research into the acquisition of Japanese grammar? Is any one particular pedagogical intervention or solution to the teaching of Japanese grammar more effective than another? What pedagogical options do we have for the teaching of Japanese grammar? This book offers a unique insight into its practical implications for Japanese language learning and teaching for applied linguists, researchers, language teaching professionals and curriculum developers alike. Alessandro G. Benati is Professor of Second Language Acquisition and Head of School of Languages and Area Studies at the University of Portsmouth. He is internationally known for his research in second language learning and teaching, with special emphases on input processing theory and the processing instruction model. He has a strong publications record with 12 established monographs, chapters and articles in international journals (Language Awareness, IRAL, Second Language Research and Language Teaching Research). Sayoko Yamashita is Professor of Humanities and Social Sciences at Jissen Women's University, Japan. She holds an Ed.D, and specializes in applied linguistics, SLA, and pragmatics. Her publications include Six Measures in JSL Pragmatics, "Politeness in classrooms-comparison between JSL and EFL classrooms" in Selected Research Papers in Applied Linguistics, and "Investigating interlanguage pragmatics ability" in Investigating Pragmatics in Foreign Language Learning, Teaching and Testing.
- Introduction -- PART I: Theoretical Perspectives -- Chapter 1. Theoretical views on the role of grammar instruction -- Chapter 2. Review of classroom-based research on the acquisition of Japanese grammar -- PART II: Research and Pedagogical Applications -- Chapter 3. Processing Instruction and the acquisition of Japanese morphology and syntax -- Chapter 4. L2 Learners and the apparent problem of morphology: Evidence from L2 Japanese -- Chapter 5. The role of linguistic explanation on the acquisition of Japanese imperfective -teiru -- Chapter 6. Grammar for reading Japanese as a second language:Variation of stance expressions utilizing to omou in different written registers -- Chapter 7. An integrated grammar-pragmatics approach: Teaching style shifting in Japanese.
Keywords: Oriental literature; South Asian Languages; Language and languages-Study and; Japanese language; Language Teaching; Language Education